2015
DOI: 10.1007/s10620-015-3644-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Adds an Element of Risk to Insulin Resistance in Colorectal Neoplasms

Abstract: IR increases the risk of CRNs, and a combination of IR and VitDdef further increases this risk. As both VitDdef and IR are modifiable risk factors, such associations may have important clinical implications in the prevention of CRNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…In a nested casecontrol study from the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial, colorectal cancer risk was significantly lower in the highest vitamin D quintile compared with the lowest quintile (11). In contrast, vitamin D level had no significant effect on colorectal cancer risk in a 2011 case-control study conducted in the USA (13) nor in a 2015 cross-sectional study conducted in South Korea (14). Similar results were obtained in our study, however, the sample size was too low to detect a small effect.…”
Section: Colorectal Cancermentioning
confidence: 88%
See 1 more Smart Citation
“…In a nested casecontrol study from the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial, colorectal cancer risk was significantly lower in the highest vitamin D quintile compared with the lowest quintile (11). In contrast, vitamin D level had no significant effect on colorectal cancer risk in a 2011 case-control study conducted in the USA (13) nor in a 2015 cross-sectional study conducted in South Korea (14). Similar results were obtained in our study, however, the sample size was too low to detect a small effect.…”
Section: Colorectal Cancermentioning
confidence: 88%
“…Evidence linking vitamin D deficiency with increased cancer risk and mortality has been found in studies conducted over the last 20-30 years (2,4). Although epidemiologic studies indicate that vitamin D levels are inversely associated with colorectal cancer (5)(6)(7)(8)(9)(10)(11)(12), several studies found inconsistent results for this association (13,14). The findings of epidemiologic studies investigating the relationship between vitamin D and breast cancer have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%